Comparative analysis of energy strategies of Kazakhstan and the European Union - Adirbaeva, А.А.; Ospanova, А.Н.; Konuratova, А.С. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2024)
Kazakhstan strives to meet the growing energy consumption and ensure sustainable economic development through the efficient use of energy resources and the development of renewable energy sources. Achieving energy security is possible through the creation of diverse and sustainable systems with an emphasis on clean environmental energy sources. The orientation of the European Union's energy strategy is to ensure a sustainable, safe and environmentally friendly energy sector capable of providing energy supply and supporting economic growth in the long term. The main problem is the need to match the implementation of the energy policy to the existing needs of an individual state or regional association. A comparison of the energy strategies of Kazakhstan and the European Union indicates that they have similar goals, but the difference lies in the peculiarities of their geographical location, the level of the economy and the policy pursued. At the same time, the main similarity of the analyzed energy strategies is the preference for alternative energy sources, for example, wind and hydrogen energy, taking into account current trends in the development of Kazakhstan and the European Union. At the same time, the exchange of relevant experience, advanced technologies and successful practices of the member states of the European Union can stimulate dynamic development in this direction. The possibilities of practical application of biogas technology are also considered. The author concludes that it is advisable for Kazakhstan and the European Union to cooperate in the process of transition to renewable energy sources. The analysis of the strategic, economic and environmental features of the transition of the regional association of European countries and a separate state of the Central Asian region to alternative energy, which may be interesting for countries with similar aspirations in the global energy sector.